Modified mandible traction with wires to treat neonatal Pierre Robin sequence: A case report - Zuo, Hailiang; Gao, Jing; Mu, Yu; Zhang, Fang; Liu, Yang (Frontiers in Surgery, 2022)
Background: Pierre Robin Sequence (PRS) is a congenital craniofacial deformity characterized by micrognathia, glossoptosis and airway obstruction. Some affected neonates are born with severe life-threatening upper airway obstruction that requires surgery. If without timely treatment, it is possible to cause not only organ damage and developmental abnormalities but also early newborn mortality. Case presentation: In this report, a 51-hours-old neonate was diagnosed with PRS, who had severe upper airway obstruction and required surgery. We performed the modified mandible traction with wires at four days old and achieved a satisfactory result in improving airway obstruction. No other complications were observed except for mild local infection. No overlap of other more complex syndromes was found, such as ocular abnormalities, hearing loss, other skeletal abnormalities, cardiac abnormalities or other atypical abnormalities. At the present follow-up until 2 years old, there were no significant differences in the maxillofacial appearance, teeth growth, breathing, feeding, growth and development between the patient and normal children. Conclusion: The modified mandible traction with wires can safely and effectively resolve micrognathia, the key to treating PRS, which is minimally invasive, simple and provides immediate relief of airway obstruction with no long term complications compared with other surgical methods. This report aims to provide more evidence of the successful treatment of neonatal PRS micrognathia by modified mandible traction with wires.